The 1st International Electronic Conference on Food Science and Functional Foods 2020
DOI: 10.3390/foods_2020-07590
|View full text |Cite
|
Sign up to set email alerts
|

Kumquat (Fortunella margarita): A Good Alternative for the Ingestion of Nutrients and Bioactive Compounds

Abstract: Citrus fruit is preferred in the choice of consumers. Kumquat (F. margarita) is an unconventional citrus of increasing consumer interest because of its exotic flavor, and its functional potential that offers health benefits to consumers. It is a fruit traditionally consumed by whole fruit (peel and pulp), giving this fruit a distinctive flavor. For this reason, this study analyzed the physical, chemical, and nutritional characteristics of kumquat (peel and pulp). The physicochemical analysis was performed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Total ash content in the current study was 2.73 ± 0.12% and it is comparable to the reported values of kumquat fruit [44]. The total ash content of the pulp was directly proportional to the presence of mineral elements.…”
Section: Morphological and Proximate Characterization Of Wood Apple Fruitssupporting
confidence: 87%
See 3 more Smart Citations
“…Total ash content in the current study was 2.73 ± 0.12% and it is comparable to the reported values of kumquat fruit [44]. The total ash content of the pulp was directly proportional to the presence of mineral elements.…”
Section: Morphological and Proximate Characterization Of Wood Apple Fruitssupporting
confidence: 87%
“…The crude fiber value obtained from the current study showed wood apple is a good source of dietary fiber, which is 3.32 ± 0.02%. Results revealed that the studied fruit pulp has a lower content of dietary fiber than kumquat fruit (5.31%) [44]. It has been proposed that consumption of fruits with high dietary fiber has various health benefits including being a carrier of antioxidants in the gastrointestinal tract to reduce risk factors related to cardiovascular and intestinal diseases [45].…”
Section: Morphological and Proximate Characterization Of Wood Apple Fruitsmentioning
confidence: 93%
See 2 more Smart Citations